A case series of mucormycosis, post COVID-19 in a tertiary care centre - Chillapalli, Lakshmi Priyanka; Mohanty, Deeganta; Kondreddy, Siri Krishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
In the 3rd wave of COVID-19 especially in India, an associated angio-invasive opportunistic infection with mucormycosis is emerged. The clinical, imaging and treatment data of 22 patients with mucormycosis was analyzed. Clinical features observed are periorbital swelling, facial pain, swelling of cheek, nasal discharge, dental pain associated with loose tooth. Imaging demonstrated PNS, orbital and intracranial extension in 100%, 55%, 20% patients respectively. All received ampho-B and underwent endoscopic debridement, 20% orbital decompression and 5% maxillectomy, 2 patients died. The association of hyperglycemia and steroid intake warrants judicious use of corticosteroids and optimal glycemic control. Good clinical outcome is achieved by aggressive surgical debridement and antifungal medication with optimal glycemic control.